GEOLOGI DAERAH PANAS BUMI ULUBELU TANGGAMUS, LAMPUNG UTARA BERDASARKAN ANALISIS METODE MAGNETOTELLURIK (MT) - Saultan Panjaitan (Pusat Survei Geologi, 2010)
Low resistivities of 0 â€“ 15 Î m are interpreted as impermeable zones, functiming as cap rocks wich is hydrothermal alteration estimated to cinsist of clay. The midle resistivity 15 â€“ 70 Î m is interpreted as permeable reservoir rocks located at 1250 â€“ 2000 metres depth. The resistivity > 1000 Î m are metamorphic carbonate rocks. Block I in south of Mt.Rendingan and Block II at around Pagaralam hot spring formed up flow zone fluid reservoir having temperature of more than 260ÂºC, and contained 80 % vapour faction.Keywords: Geothermal,resistivity, impermeable, cap rock, hydrothermal alteration